Juridical Analysis of Consumer Responsibility for The Cash on Delivery (COD) System in E-Commerce Buying and Selling - Putri Sari Asih; Mutimatun Niami (Universitas Muhammadiyah Surakarta, 2024)
The aim of writing this article is to analyze consumer responsibility for the Cash On Delivery (COD) system in e-commerce buying and selling The problem that often arises in Cash On Delivery (COD) in e-commerce buying and selling is the lack of clarity in efforts to resolve disputes between consumers and sellers when there is dissatisfaction or problems with the goods received. In this writing, a normative juridical approach is used. Writing this article involved an analysis of legal regulations relating to the problem under study, and a study of existing literature. There are many consumers who violate their responsibilities as consumers in the COD system in e-commerce buying and selling. As recipients of goods, consumers have responsibilities such as paying on time in the COD system, and compensating for losses due to default. The suggestion put forward is to increase supervision and law enforcement against fraudulent or fraudulent practices in the COD system. In addition, it is important to strengthen cooperation between relevant parties, including the government, sellers and consumers, in developing guidelines and standards that promote fair and safe e-commerce buying and selling transactions.